Strategi Pengembangan Objek Wisata Air Terjun Sarambu Alla’ Berbasis Ekowisata: Bukti Empiris Kabupaten Luwu Utara. - intan maharani; M. Fathur Rohman; Windi; Ibnu Haidir (Institut Agama Islam Negeri Palopo, 2024)
This research aims to determine strengths, weaknesses, opportunities and threats. This type of research is quantitative research. The source of research data was obtained from direct interviews with the people of Kalotok Village, South Sabbang District, North Luwu Regency. From the results of this research, based on the results of the SWOT analysis by calculating the IFAS (strengths and weaknesses) and EFAS (opportunities and threats) scores, eight alternative strategies were produced and showed a positive value (+) so that the strategy for developing the Sarambu Alla' waterfall tourist attraction supports village income. Kalotok is in quadrant I, namely between strength and opportunity (SO) strategies. 1) Maximizing the management of tourism potential by adding several other tourist attractions. 2) Utilizing human resources in managing tourist attractions. 3) Improving infrastructure and facilities through collaboration with the provincial government. 4) Improving the quality of professional staff in managing tourist attractions to reduce environmental damage due to uncontrolled development. 5) Carrying out community development regarding the management of the Sarambu Alla' Waterfall tourist attraction 6) development and construction of environmentally friendly tourist attractions 7) Utilizing human resources in managing tourist attractions 8) adding new attractions and facilities gradually so that they are ready to compete with other tourist attractions . It can be seen that the Sarambu Alla' tourist attraction in Kalotok Village, South Sabbang District, North Luwu Regency has many opportunities that need to be utilized as well as possible.